Metformin added to insulin therapy for type 1 diabetes mellitus – based on literature and own expe- rience - Otto-Buczkowska, Ewa (European Journal of Clinical and Experimental Medicine, 2010)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Insulin administration is the primary therapy for type I diabetes mellitus (TIDM). Current availa-ble insulin therapies do not successfully enable patients with TIDM to reach glycemic goals without side effects such as hypoglycemia and weight gain. Type 1 diabetes is recognised to include an element of insulin resistance. Insulin resistance is an independent risk factor for the development of macro- and microvascular complications of Type 1 diabetes and may also contribute to the development of the dis-ease. Metformin is a commonly prescribed oral hypoglycaemic agent used to treat type 2 diabetes melli-tus. Addition of metformin to insulin in patients with type 1 diabetes mellitus improves metabolic con-trol. Metformin acts by promoting glucose utilization and reducing hepatic glucose production. In type 1 diabetes, addition of metformin to insulin therapy, to improve insulin sensitivity, reduces insulin-dose requirement. Metformin can contribute towards improving glycaemic control in patients with TIDM.